Effects of Thermal Acclimation on the Tolerance of Bactrocera zonata (Diptera: Tephritidae) to Hydric Stress - Ben-Yosef, Michael; Verykouki, Eleni; Altman, Yam; Nemni-Lavi, Esther; Papadopoulos, Nikos T.; Nestel, David (Frontiers in Physiology, 2021)
Insects, similarly to other small terrestrial invertebrates are particularly susceptible to climatic stress. Physiological adjustments to cope with the environment (i.e. acclimation), together with genetic makeup eventually determine the tolerance of a species to climate stress, and constrain its distribution. Temperature and desiccation resistance in insects are both conditioned by acclimation and may be interconnected, particularly for species inhabiting xeric environments. We determined the effect of temperature acclimation on desiccation resistance of the peach fruit fly (Bactrocera zonata, Tephritidae) - an invasive, polyphagous pest, currently spreading through both xeric and mesic environments in Africa and breaching into the Eurasian continent. Following acclimation at three constant temperatures adult survival was monitored in extreme dry (<10%RH) and humid (>90%RH) conditions. We found that flies acclimated at higher temperatures were significantly heavier, and had significantly elevated lipid and protein levels. Overall life expectancy was significantly shortened when flies were assayed under desiccating compared to high humidity conditions. Additionally, acclimation temperature significantly affected the survival of males and females, and flies maintained at 30 oC survived longer compared to 20 oC and 25 oC -habituated counterparts. However, the effect of acclimation temperature was similar at both dry and humid environments. We conclude that acclimation at 30 oC prolong the survival B. zonata, at both xeric and mesic environments probably through modulating feeding and metabolism, allowing for accumulation of larger energetic reserves. Physiological mechanisms of water management may also be affected by acclimation and contribute to desiccation resistance. Our study set the basis to understand the current geographic range of B. zonata from the hydric perspective, and to evaluate the invasion potential of this pest.